Analisis Penerapan Akad Mudhorobah Muthlaqoh Pada Produk Tabungan Ib Hijrah Prima di PT. Bank Muamalat Indonesia - Hari Basuki; Maslihatun Khasanah (JPSDa: Jurnal Perbankan Syariah Darussalam, 2021)
Mudharabah Muthlaqah is where shahibul maal gives full discretion to the manager (mudharib) to use the funds in a business which he considers to be good and profitable. However, the manager is still responsible for managing it in accordance with normal healthy business practices (uruf). In the DSN-MUI review of the implementation of the muthlaqoh mudhorobah contract on the savings from the prime hijrah, the researchers analyzed that it was appropriate. Because based on the DSN-MUI fatwa regarding justified savings are savings based on mudhorobah and wadi'ah principles, while unjustified savings are savings based on interest calculations. research using qualitative research methods that use descriptive analysis. The results of this study indicate that the application of the mudhorobah muthlaqoh agreement on iB hijrah prima savings in calculating the profit sharing that must be considered is HI-1000 (read ha-i-thousand) which every month there is always a change and based on the average customer balance at each the month with the existence of the ratio waad.